Updating knowledge on growth, population dynamics, and ecology of the blue and red shrimp, Aristeus antennatus (Risso, 1816), on the basis of the study of its instars. (30th July 2012) - Orsi Relini, Lidia; Mannini, Alessandro; Relini, Giulio
Abstract Both national (GRUND) and international (MEDITS) trawl surveys carried out in the Italian seas since 1994 have produced consistent and rather homogeneous samples of red shrimps (per season, gear, and methods to ascertain abundance). Study and discussion of data regarding Aristeus antennatus (Risso, 1816) from Ligurian fishing grounds during the REDs project (FISH/2004/03‐32) made it possible to verify how key instars of the life of the female shrimp can be recognized from length frequency distributions derived from trawl surveys, allowing the age distributions to be split up. The segment of life that can be studied spans ages 1 and 10 and includes 20 instars, but larger sizes have been found which may extend the life span another 3 years. After age 5, only one growth instar per year occurs. Based on our study of the instars, we developed a size/age key for A. antennatus and used it to derive a von Bertalanffy growth function, total mortality rates and exploitation rates. Our results are related to basic biological and ecological characteristics of this species. Large individuals (females ≥50 mm CL at age 5 onward) present in a considerable percentage in the Ligurian Sea, are very important because (i) their fecundity is very high and therefore greatly influences the reproductive potential and (ii) they represent commercially the most valuable part of the catch. In addition, substantial relationships between the life history of A. antennatus and local oceanographic processes exist because the long life span of the species enlarges the area to which eggs and larvae are transported in surface currents, as well as the active return movements in deep waters where adult life mainly takes place. In the study area, the Northern Current provides the possibility of great horizontal displacement of A. antennatus eggs, larvae and early juveniles and, in general, attention to surface circulation may help to identify affinities in distant Mediterranean populations. This study presents A. antennatus in terms of a resource on the move at a Western Mediterranean scale.